Kepribadian Negosiator - Hamdan, Yusuf (Mediator, 2007)
Negotiation has an important role on human interaction in order to fulfill their needs of life. Negotiation enabled cooperation and in turn, resolved conflicts as well. This paper examines a vital part of negotiation, namely negotiator’s personality. Although tactic and strategy are important, the negotiator’s personality played a more vital role. A good tactic and strategy will be useless in the hands of negotiator whose personality isn’t matched perfectly with negotiation purposes. The description toward negotiator personality covered a discussion toward negotiator’s attitude, and confidence.